(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
In this article we are talking about such a complex kind of mental activity as translation. The emphasis is on the fact that this is one of the types of speech activity. The types of translation, including the technical one, which are most often used at higher levels, are analyzed. Speaking of speech I would like to pay attention to the translation as one of the types of speech activity. Translation is also a unique tool for the development of linguistic and linguistic competence. Translation activities are the same speech activity as the author’s, and, perhaps, more important and meaningful. It should be borne in mind that translation is a multidimensional and multidimensional type of human activity that involves, to a certain extent, the reconstruction of the translator’s activities of the author, while respecting the original and, at the same time, taking into account the peculiarities of his culture. Today distinguish two main types of translation: educational and technical. Training translation is a translation from Russian into Ukrainian, that is, into the language that is being studied. This type makes it possible to obtain from students the use of those structures, which need to pay attention, to activate language means. First, by translating, students are forced to look for means to adequately convey thoughts in the language they are learning. Secondly, in the process of translation, the attention of students is drawn to a similar and distinctive in two languages. In the process of exchange of scientific and technical information between specialists, the role of an intermediary is performed by a technical translator. It should be remembered that most often translate the latest information contained in foreign scientific publications. In order to qualitatively make a technical translation, the specialist must possess such knowledge, qualities and skills: to be knowledgeable in a certain field of knowledge and production, that is, to have a professional terminology and be able to use different types of dictionaries; master all types of technical translation. The information industry of modern society puts linguistics, as well as in the fields of computer science, psychology, sociology, philosophy, fundamentally new applied management problems that arise in connection with the automation of intellectual activity. One of them is the machine translation, which is based on the connection of linguistic problems of the MP with the general problems of linguistics - on the one hand, and with the general problems of computer science - on the other. Therefore, the systematic analysis of the research object consists in the unity of empirical and theoretical, linguistic and extra-linguistic, integral and differential in the description of information influence.